2013
DOI: 10.1093/eurjhf/hft105
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular hypertrophy and failure abolish cardioprotection by ischaemic pre‐conditioning

Abstract: AimsWe aimed to investigate the response to ischaemia-reperfusion (IR) and ischaemic pre-conditioning (IPC) in the hypertrophic and failing right heart. Methods and resultsMale Wistar rats underwent sham operation, moderate pulmonary trunk banding (mPTB), or severe PTB (sPTB). Four weeks after surgery, hearts were quick-frozen (n ¼ 28) for biochemical analysis of key salvage pathways or isolated and perfused in a Langendorff set-up (n ¼ 46). We randomized perfused hearts to IPC (2 × 5 min of global ischaemia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…This agrees with previous studies 25,27 and suggests an adaptive remodeling of the right ventricle with preserved systolic function.…”
Section: A C C E P T E Dsupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with previous studies 25,27 and suggests an adaptive remodeling of the right ventricle with preserved systolic function.…”
Section: A C C E P T E Dsupporting
confidence: 93%
“…23,24 These findings are comparable to both animals and humans with decompensated RV hypertrophy and failure 5,21,25,26 . Rats subjected to the mild banding presented with elevated RV pressures, increased RV weight, reduced TAPSE, but preserved cardiac output.…”
Section: A C C E P T E Dsupporting
confidence: 54%
“…HF is defined as "a complex clinical syndrome that can result from any structural or functional cardiac disorder that impairs the ability of the ventricle to fill or eject blood" I/R injury has been reported over 3 decades, that the myocardial injury and cardiomyocyte death paradoxically occurs with the acute reperfusion of ischemic myocardium, and one or more cycles of ischemia-reperfusion preconditioning (IPC) or pharmacological conditioning have been considered as powerful cardioprotective strategy for reducing infarct size, attenuating cardiomyocyte injury [6]. However, the cardioprotection of IPC and opiate preconditioning was impaired in pathological myocardium, including postinfarct remodeled hearts [7], hyperglycemia [8], right ventricular hypertrophy and failure [9].…”
Section: Introductionmentioning
confidence: 99%
“…The myocardial structural and signal transduction changes will render the heart more sensitive to IRI and suppress the effect of cardioprotective strategies. A very meaningful study performed by Andensern et al (4) demonstrated that right ventricular hypertrophy increased IRI. Cardioprotection by IPC was abolished in the failing but not the compensated hypertrophic right ventricular of the rat hearts.…”
Section: Hypertension and Myocardial Hypertrophymentioning
confidence: 95%
“…Despite these landmark results are consistently proved in experimental models, it is a pity that conditioning application is restricted and the protection is diminished in clinical settings such as cardiac operation and elective percutaneous coronary intervention. The main reason is that the aging population and the growing prevalence of comorbidities such as ageing (4), diabetes (5), hypercholesterolemia (6), and heart diseases (7,8), which are not present in animal studies. It has been speculated that pathological processes resulting in fundamental signaling molecular alteration may affect the development of IRI and the responses to cardioprotective interventions.…”
mentioning
confidence: 99%